Sonoelectrochemically enhanced electrocatalytic processes: The Pb(IV) catalyzed cleavage of 1,2-cis-cyclopentanediol at graphite and glassy carbon electrodes - Marken, F; Compton, R; Buston, J; Moloney, M (1998)
In this study, the electrocatalytic (EC′-type) carbon-carbon bond cleavage of cis-1,2-cyclopentanediol by Pb(IV) benzoate generated in situ is shown to be possible under extremely fast mass transport conditions. Based on the comparison of data obtained experimentally and by the numerical simulation of sonoelectrochemical limiting currents with commercially available software (Digisim 2.0), excellent agreement with the theoretical model of a planar diffusion layer can be achieved and allows the straightforward prediction and optimization of sonoelectrochemcial processes involving homogeneously coupled chemical steps. The ultrasonic cleaning of the electrode surface strongly affects the Pb deposition process at glassy carbon and basal plane pyrolytic graphite electrodes, but is not efficient enough to prevent electrode fouling which accompanies the anodic process at positive potentials. The overall rate and efficiency of the electrochemical process is enhanced due to fast mass transport in the presence of ultrasound.